Pengaruh Komponen Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi Provinsi Bali - Lilya Santika Dewi, Nyoman; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 3, Maret 2014 (pp. 76 - 123), 2014)
Human development is one of the indicators of the achievement of economic development. Although human development was increased each year from 2004 – 2012, but human development inequality still visible between the district/city of the province of Bali. This research aims to know the influence of the health index, an index of education and purchasing power indices of Bali Province economic growth simultaneously and partial. Data used are sondary data from the central statistical agency of Bali province. Methods of analysis used is the method of regression analysis techniques and associative data panel with Pooled Least Square method. Based on the results of sports data, acquired that health index, an index of education and purchasing power index is the simultaneous and significant impact on the economic growth of the province of Bali while the partial test results obtained that the education index and index of purchasing power of society in a positive and significant impact on economic growth, while the health index did not influence significantly the economic growth of the province of Bali. Existence of a positive relationship between economic growth and human development and human development must be equitable policies to the attention of the Government.
Keywords: human development, economic growth